Influence Of Price, Product Quality and Brand Image Towards Oil Customer Loyalty Fried Palmanco In Medan City In East Medan District - Triara Juniarsih; Satrio Wicaksono; Adika Fajar Putra (TALENTA Publisher, Universitas Sumatera Utara, 2025)
This research aims to determine and analyze the influence of price,product quality and brand image on customer loyalty for PalmancoCooking Oil in Medan City in East Medan District. This research isassociative research and the type of data used is quantitative. The dataused was obtained from interviews, surveys and distributingquestionnaires. The analytical method used is descriptive analysis andmultiple linear regression analysis. The population of this research isthe people of Medan city, especially in East Medan District, who usePalmanco cooking oil products. The number of samples in this studywas 119 people using a purposive sampling technique with the criteria:aged over 20 years and had purchased Palmanco cooking oil productsat least 3 times. The results of this research show that simultaneouslyPrice, Product Quality and Brand Image have a positive and significanteffect on Customer Loyalty for Palmanco Cooking Oil in Medan Cityin East Medan District. Partially, Price, Product Quality and BrandImage have a positive and significant effect on Customer Loyalty forPalmanco Cooking Oil in Medan City in East Medan District.